Management of Vascular Risk Factors in the Carotid Revascularization Endarterectomy Versus Stenting Trial (CREST). Issue 6 (26th November 2014) - Meschia, James F.; Voeks, Jenifer H.; Leimgruber, Pierre P.; Mantese, Vito A.; Timaran, Carlos H.; Chiu, David; Demaerschalk, Bart M.; Howard, Virginia J.; Hughes, Susan E.; Longbottom, Mary; Howard, Annie Green; Brott, Thomas G.
Abstract : Background: The Carotid Revascularization Endarterectomy Versus Stenting Trial (CREST) is a multicenter randomized trial of stenting versus endarterectomy in patients with symptomatic and asymptomatic carotid disease. This study assesses management of vascular risk factors. Methods and Results: Management was provided by the patient's physician, with biannual monitoring results collected by the local site. Therapeutic targets were low‐density lipoprotein, cholesterol <100 mg/dL, systolic blood pressure <140 mm Hg, fasting blood glucose <126 mg/dL, and nonsmoking status. Optimal control was defined as achieving all 4 goals concurrently. Generalized estimating equations were used to compare risk factors at baseline with those observed in scheduled follow‐up visits for up to 48 months. In the analysis cohort of 2210, significant improvements in risk‐factor control were observed across risk factors for all follow‐up visits compared with baseline. At 48 months, achievement of the low‐density lipoprotein cholesterol goal improved from 59.1% to 73.6% ( P <0.001), achievement of the systolic blood pressure goal improved from 51.6% to 65.1% ( P <0.001), achievement of the glucose goal improved from 74.9% to 80.7% ( P =0.0101), and nonsmoking improved from 74.4% to 80.9% ( P <0.0001). The percentage with optimal risk‐factor control also improved significantly, from 16.7% to 36.2% ( P <0.001), but nearly 2 of 3 study participants did not achieve optimal control during the study. Conclusions: Site‐based risk‐factor control improved significantly in the first 6 months and over the long term in CREST but was often suboptimal. Intensive medical management should be considered for future trials of carotid revascularization. Clinical Trial Registration: URL: ClinicalTrials.gov. Unique identifier: NCT00004732.